Analisis Pola Kemitraan Bibit Albesia antara CV Flora Bali di Kabupaten Karangasem dengan UD Tunas Jaya di Kabupaten Klungkung - WINAYA, MADE NGURAH SABDA; ARTINI, NI WAYAN PUTU; WIJAYANTI, PUTU UDAYANI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.4, Oktober 2018DO - 10.24843/JAA.2018.v07.i04.p11, 2018)
Analysis of Albesia Seed Pathership Pattern Between CV Flora Bali in Karangasem Regency with UD Tunas Jaya in Klungkung Regency Cultivation of forest crops can involve various parties, among others, business entities, government, non-governmental organizations and private parties One of the private parties who market forest tree seeds is UD Tunas Jaya. Business partnership relationship between UD Tunas Jaya with CV. Flora Bali in its journey there has been no further analysis of the mechanism of partnership and what benefits have been obtained. This study aims to determine the pattern of partnership business seeds of forest plants between CV. Flora Bali with UD.Tunas Jaya in Pempatan Village, Rendang Sub-district, Karangasem Regency. This research is descriptive conducted at CV Flora Bali and Tunas Jaya by collecting data through in-depth interview and observation. Quantitative data analysis is done by using analysis of farming. The result of the research shows the partnership pattern that has been done between CV Flora Bali and UD Tunas Jaya in the form of Subcontract which is the pattern of partnership relationship between the business partner company that is UD Tunas Jaya with the business partner that produces the seed of forest plant that is CV Flora Bali. The distinctive feature of this subcontract partnership form is to make a joint contract that includes volume, price and time. CV Flora Bali with UD Tunas Jaya in the subcontract partnership pattern is the increase of productivity, labor efficiency and time, the seeds produced in the quality, quantity, and continuity are acceptable to the consumer, social relationships, and increase the income and welfare for the perpetrator Partnership.